2018
DOI: 10.1038/s41598-018-31544-w
|View full text |Cite
|
Sign up to set email alerts
|

Genetic insights into underground responses to Fusarium graminearum infection in wheat

Abstract: The ongoing global intensification of wheat production will likely be accompanied by a rising pressure of Fusarium diseases. While utmost attention was given to Fusarium head blight (FHB) belowground plant infections of the pathogen have largely been ignored. The current knowledge about the impact of soil borne Fusarium infection on plant performance and the underlying genetic mechanisms for resistance remain very limited. Here, we present the first large-scale investigation of Fusarium root rot (FRR) resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Notably, this is not the first report of a link between root biomass and CR tolerance. A recent study in bread wheat found that genotypes with a higher total root biomass were more resistant to fungal infection [4]. This could be due to higher lignin/fiber content at the cellular level presenting a physical barrier for fungal growth and therefore providing enhanced resistance.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, this is not the first report of a link between root biomass and CR tolerance. A recent study in bread wheat found that genotypes with a higher total root biomass were more resistant to fungal infection [4]. This could be due to higher lignin/fiber content at the cellular level presenting a physical barrier for fungal growth and therefore providing enhanced resistance.…”
Section: Discussionmentioning
confidence: 98%
“…Root rot of corn is caused by F. meridionale and F. boothii, and both root rot and kernel rot -by Trichoderma sp., Penicillium sp., Pyrenochaeta indica, F. moniliforme, F. graminearum and oxysporum. These examples of synergetic interactions between the agents of plant diseases, causing the diseases of whole complexes, may be found to have achieved higher prevalence than expected, and the understanding of the main mechanisms may have important consequences in the ¿ eld of plant disease epidemiology and ¿ ghting diseases [13].…”
mentioning
confidence: 99%
“…This could possibly be a result of the variability due to CR infection during early growth stages. However, alternative root growth patterns including higher total root biomass seem to have a reduced susceptibility to CR and therefore increased yield (Voss-Fels et al, 2018a).…”
Section: Seminal Root Angle Qtl Qsra-6a Involved In Durum Performancementioning
confidence: 99%
“…Crown rot continues to be a destructive disease globally and has been particularly damaging in Australia due to dramatic changes in cropping systems, including intensive cropping, the introduction of minimum tillage practices and a rapidly changing climate (Verrell et al, 2017;Voss-Fels et al, 2018a). Zhao et al (2017) estimated a yield reduction as a result of global warming in the major crops such as rice, wheat and maize of 3.2%, 6.0% and 7.4%, respectively, for each degree Celsius temperature increase.…”
Section: The Crown Rot Qtl Qcr-6b Is a Key Genomic Region Modulating mentioning
confidence: 99%
See 1 more Smart Citation